PENINGKATAN PRODUKTIVITAS PERTANIAN DAN KUANTITAS PRODUKSI POKTA MELALUI PEMANFAATAN TOMCAR4 (KOTORAN KAMBING, AIR CUCI BERAS, DAN EM4) - Rahma Sandhi Prahara; Aulia Herdiani; Andri Imam Setiawan; Moh. Toha (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
Organic fertilizer made from goat manure, combined with rice washing water and EM4 (Tomcar4), aims to boost agricultural productivity and Pokta fertilizer production. Organic fertilizer provides a sustainable solution to challenges such as limited access to subsidized fertilizers and high costs of non-subsidized ones due to the energy crisis. However, its adoption faces barriers, particularly in rural areas with limited access to information and technology. This program employs the ABCD method to enhance community capacity in producing and using organic fertilizer as a long-term strategy. The Tomcar4 initiative has produced 1.5 quintals of fertilizer, a modest quantity that contributes to the Jaya Dokkare farmer group's reserves. While production volume remains small, the program primarily focuses on educating and empowering farmers to independently produce organic fertilizer, ensuring sustainable practices in the future.